COMPORTAMENTO DE AMAMENTAÇÃO DE BEZERROS NELORE E CRUZADOS - SANTOS, Camylla Silveira,; CASTRO, Micheline Feitosa,; QUEIROZ, Maria Carla Elias,; ALMEIDA, Gabrielly Benevides,; SILVA, Milena Vitória,; OLIVEIRA, Dalton Mendes, (ANAIS DO ENIC, 2024)
-